ANALISIS PERAN TEMAN SEBAYA PERKUMPULAN KELUARGA BERENCANA INDONESIA (PKBI) DALAM MENANGANI KEKERASAN GENDER DI KOTA MAKASSAR - Amriani, Lisa; Torro, Supriadi; Arifin, Zainal (Universitas Negeri Makassar, 2025)
This research aimed to identify: 1) The role of Indonesian Family Planning Association (PKBI) peers in addressing gender-based violence in Makassar City, and 2) The driving and inhibiting factors influencing PKBI peers in handling gender-based violence in Makassar City. This study was qualitative in nature and employed a descriptive approach. The number of informants in this research was 11 people, selected using purposive sampling techniques, with the criteria including PKBI youth administrators, PKBI program implementers, staff of the Makassar City UPTD PPA, and victims of gender-based violence. The validity of the data was examined using triangulation, including technique triangulation and source triangulation. Data were collected through observation, interviews, and documentation. Data analysis included data condensation, data presentation, and conclusion drawing. The results of the study showed that the roles of PKBI peers in addressing gender-based violence in Makassar City included: a) the role as counselors, b) the role as medical personnel, c) the role as facilitators, d) the role as motivators, and e) the role as educators. The driving factors included: a) humanitarian pioneering, b) inter-institutional synergy, c) institutional networks or connections, d) program demands, and e) donor support. Meanwhile, the inhibiting factors in addressing gender-based violence in Makassar City included: a) the busy schedules of PKBI youth, b) victims’ unwillingness to report, c) victims’ withdrawal during the handling process, and d) limited funding.